사료작물 사일리지의 단백질 분획 및 Borate-phosphate Buffer 추출이 In vitro 발효성상, Gas 발생 그리고 분해율에 미치는 효과 - 김광림; 지병주; 오영균; 홍성구; 송만강; Shinekhuu, Judder; Jin, Guang-Lin; Ji, Byung-Ju; Li, Xiangzi; Oh, Young-Kyoon; Hong, Seong-Ku; Song, Man-Kang (Journal of animal science and technology, 2009)
Protein fractionation was evaluated from whole crop silages of rye (RS), wheat (WS), triticale (TS), oat (OS), barley (BS), and rice straw silage (RSS), and in vitro trial was carried out to examine the effect of silage and extraction of soluble protein on fermentation characteristics, total gas production and degradation. Soluble protein of silages was extracted with borate-phosphate buffer, and fermentation characteristics, gas production and degradation of silages were estimated by incubating anaerobically the mixed solution of strained rumen fluid and artificial saliva (1:1, v/v) containing dried and ground silages placed in nylon bag at $39^{°}C$ up to 48h. Soluble protein (SP) content was lowest for RSS as 2.11% in total CP compared to those for other silages. Highest A fraction (NPN) was observed from RS (74.33% of total CP) while those from TS and RSS were relatively low (48%). B2 fraction was relatively higher for RS, RSS and WS than for TS and BS. $B_3$ fraction was lowest in WS among silages. C fraction (27.07) in RSS was higher than in other silages (1.40~9.93%). pH in incubation solution was increased (P<0.01~P<0.001) for extracted silages up to 12h but decreased (P<0.01) at 48h for non-extracted ones. Contents of ammonia-N (P<0.001) and total VFA (P<0.01~P<0.001) were higher for non-extracted silages than for extracted ones. Acetate proportion was increased (P<0.001) in buffer extracted silages while those of propionate and butyrate were decreased (P<0.001) up to 24h incubation. Increased (P<0.001) total gas production was obtained from non-extracted silages up to 12h while gas production was increased (P<0.01) in extracted ones thereafter. In vitro degradation of dry matter and CP was increased (P<0.001) in non-extracted silages but that of neutral detergent fiber was increased (P<0.001) in extracted ones without difference among silages. Difference in mean values of degradability for each silage prior to- and post extraction with borate buffer, however, was not found among silages. It may be concluded that high NPN content of silages may reduce the protein availability in silages and borate buffer soluble components in silages can stimulate the early stage of fermentation. 본 시험은 여러 종류(호밀, RS; 볏짚, RSS; 소맥, WS; 트리티케일, TS; 귀리, OS; 청보리, BS)의 사일리지를 대상으로 단백질을 분획(fractionation)하고, in vitro 방법으로 buffer 추출 전과 추출 후의 사일리지를 배양하였을 때 반추위 미생물에 의한 발효성상, 가스발생량 및 분해율을 조사하고자 실시되었다. 사일리지의 가용성 물질은 boratephosphate 용액으로 추출하였으며, 반추위액과 인공 타액이 동일한 비율로 구성된 배양액을 혐기적인 조건에서 48시간동안 배양($39^{°}C$)하면서 발효 성상과 nylon bag을 이용한 사일리지의 in vitro 분해율을 조사하였다. 사일리지의 soluble protein (SP) 함량은 RSS에서 총 CP 함량 중 2.11%로 가장 낮았으며, RS와 BS 및 OS에서는 7% 이상의 높은 함량을 보였다. 또한 A fraction (NPN)은 RS에서 총 CP의 74.33%로 가장 높았으나 TS 및 RSS의 NPN 함량은 48% 정도로 비교적 낮았다. Buffer 불용성 단백질(IP) 중 B2 fraction은 RS, RSS 및 WS에서 총 CP의 7% 이상으로 비교적 높았던 반면 TS (1.45%)와 BS (2.13%)에서 매우 낮았다. 이와는 달리 $B_3$ fraction은 WS (4%)를 제외하고는 다른 사일리지에서 5.99~15.20%의 함량을 보였다. 체내 이용성이 매우 낮은 C fraction은 볏짚 사일리지(RSS)에서 27.07%로 다른 종류의 사일리지(1.40~9.93%)에 비하여 현저히 높은 수준이었다. 배양 12시간 까지는 추출 전에 비하여 추출 후의 사일리지 배양액에서 pH가 높았으나 (P<0.01~P<0.001) 48시간에는 오히려 추출 전의 사일리지 배양액의 pH가 낮았다(P<0.01). 배양액의 ammonia-N는 모든 사일리지에서 추출 전의 농도가 추출 후의 농도에 비하여 현저히(P<0.01~P<0.001) 높았으나 사일리지 종류에 의한 영향을 받지 않았다. 모든 사일리지에서 추출 후에 비하여 추출 전의 VFA 농도가 현저히 증가되었다(P<0.01~P<0.001). Acetate의 조성 비율은 buffer 추출 전에 비하여 배양 24시간까지 추출 후 모든 사일리지에서 높았던 (P<0.01~P<0.001) 반면 propionate와 butyrate 비율은 배양 24시간까지 추출 전에 더 높았다(P<0.001). 배양 12시간까지는 buffer 추출 전의 사일리지로부터 더 많은(P<0.01~P<0.001) 양의 gas가 발생되었지만 그 후로(24~48시간)는 오히려 buffer로 추출된 후의 사일리지에서 발생량이 더 많았다(P<0.01). 추출 후에 비하여 추출 전 사일리지의 DM과 CP 분해율이 현저히(P<0.001) 높았으나 NDF 분해율의 경우 오히려 추출 후의 사일리지에서 높았다(P<0.001). 그러나 각 사일리지에 대한 buffer 추출 전 후의 평균치에서는 사일리지 간에 차이가 없는 것으로 나타났다. 본 시험의 결과로 미루어 보아 사일리지로 인해 현저히 증가된 NPN 함량이 사일리지의 단백질 이용율을 크게 낮출 것으로 보이며, 단백질을 포함한 buffer 가용성 물질은 사일리지의 초기 발효를 크게 촉진할 수 있는 것으로 여겨진다.